An assessment of coastal headland along Negeri Sembilan coastline in Malaysia for tidal energy extraction / Goh Hooi Bein - Goh , Hooi Bein (2021)
Large tidal currents usually can be observed around coastal headlands due to their geometrical effects. This coastal feature may become attractive tidal energy extraction site for electricity generation. Straits of Malacca consists of some recognized tidal stream energy sites in the world, but their detailed characteristics were previously unknown. This thesis focuses on the exploration of tidal stream energy along Negeri Sembilan coastline. The main objectives of this study is to achieve tidal current turbine deployment with maximum tidal energy extraction exploitability with minimal environmental impact. Resource assessment was done at multiple headlands along Negeri Sembilan coastline in the first stage of the study using a detail hydrodynamic numerical model. The model was then refined at a key site, the Tg Tuan Headland, the most promising tidal stream site among the four selected headlands. The country can save about RM 13.4 million (~ USD 3.2 million) of natural gas per year as a total amount of 185 GWh or 660 TJ of natural gas can be replaced every year with tidal current turbine installation at Tg Tuan Headland. Artificial energy extraction was parameterised at the sub-grid-scale via porous plate in the developed numerical model. This study was set to measure the energy production potential and to gauge the effects of tidal energy extraction in different configurations: depth, array in different numbers of row, and single and cumulative tidal arrays on the coastal environment. The result on depth effect assessment showed that depth of deployment is not significant in changing the current speed and extractable electrical power. The difference is less than 0.002 m/s and 0.02 MW compared D1 (highest) and D8 (lowest) mean current speed and electrical power extraction for about 7 m difference. For array effect assessment, diminishing returns on the power generation was obtained, where peak power production from L6 (9.2 MW) was 97% of its total electrical power capacity, less than the corresponding values for each row of the smaller array, even though considerably low extraction was made with considerably large gap 10D was assumed in between each turbine. Comprehensive numerical models were developed to investigate the interaction risk of single and cumulative tidal array (1.5 km x 1.5 km) effect along the Negeri Sembilan Coastline, where, the sites are with combination of higher and lower peak velocities. Several aspects have been studied that included hydrodynamic mechanisms, bed shear stress, sediment transport and monsoonal variation in the assessment. For cumulative impact assessment, the analysis results showed positive exploitability for implementing sites with combination of higher and lower peak velocities with close proximity (~ 10 km), where the interference to each tidal array is less than 10% to each other. The results from this study can be used as basis to provide spatial and temporal information for further assessment of tidal energy extraction impacts to the environment. The outcomes yielded from this study would be a good source of reference to the authorities in decision making related to deployment of tidal turbine near Tg Tuan Headland.